Association between the Big Five personality traits and suicide‐related behaviors in Japanese institutionalized youths - Masaru Takahashi; Kasumi Imahara; Yukiko Miyamoto; Kayoko Myojo; Michiko Yasuda (PCN Reports, 2024)
Abstract Aim Inmates in correctional institutions experience higher rates of suicide attempt (SA), suicidal ideation (SI), and nonsuicidal self‐injury (NSSI) than the general population. This study aimed to examine the association between the Big Five personality traits and suicide‐related behavior, and to estimate the prevalence rate of such behaviors among Japanese institutionalized youth. Methods The participants were 436 youths who had been admitted to four juvenile classification homes (JCHs) between September 2021 and March 2023; they were asked to respond to a self‐report questionnaire after obtaining informed consent. Results A total of 8.1% and 19.3%, 29.4% and 44.7%, and 46.3% and 75.3% of males and females had experienced SA, SI, and NSSI in their lifetime, respectively. Females reported significantly higher instances of suicide‐related behaviors than males considering all suicide‐related behaviors. Logistic regression analyses revealed that neuroticism significantly increased the odds ratios for SA, SI, and NSSI on controlling for sex, age, and number of admissions to JCHs. For NSSI, the odds ratio for agreeableness was significantly lower than 1, indicating a lower probability of NSSI. Conclusion The findings of our study demonstrate that neuroticism, one of the Big Five traits, was consistently and significantly associated with all suicide‐related behaviors, including SA, SI, and NSSI, among youth offenders, while agreeableness was found as a protective factor only against NSSI. The results of this study might help correctional officers identify justice‐involved youth at higher risk for suicide and allow the development of early interventions to prevent suicide.